Microneurosurgical Planning in Toe-to-Hand Transplantation: Axonal Population of Digital Nerves in the Fingers and Toes - Wei, Fu-Chan; Chien, Yu-Yi; Ma, Hae-Shya; Dellon, A. Lee (Journal of Reconstructive Microsurgery, 2012)
Although toe-to-hand microvascular transplantation is now an accepted and successful reconstructive strategy for the thumb, there remains varying success in recovery of sensibility. The purpose of the present study was to provide an anatomic basis for analyzing neurotization of the great toe or the second toe with the digital nerves of the fingers and hand. Axon counts were obtained from donor and recipient nerves during reconstructive procedures. Sixty-seven upper- and eighty lower-extremity nerves were analyzed. No statistical difference was found between the mean number of axons between the thumb and the index finger; however, the thumb had significantly more (p < 0.001) axons than the middle or the ring finger. The great toe had significantly more axons than the second toe (p < 0.001). The common plantar digital nerve had significantly more axons than a digital nerve (p < 0.001). The thumb had significantly more axons than the great toe (p < 0.001). The thumb had significantly more axons than the second toe (p < 0.001). Numerical data are now available for strategic planning of toe transplantation, and direct neurotization from the dorsum of the hand to the digits.
Keywords: toe-to-thumb; digital nerve; nerve fiber count; sensory reeducation